Auditoria de Avaliação de Gestão: o uso de indicadores de desempenho nos processos de gestão das Unidades Jurisdicionadas da Marinha do Brasil - Fajardo, Jeisom de Melo (2011)
Many are the shapes and the theoretical concepts concerning the audit. In the public sector it becomes more important because it is the analysis of acts and events that involve the management of funds from the taxpayer's pocket. With the introduction of some paradigms brought in from abroad to Brazil within the meaning of control and audit, needs assessment were born a few more ubiquitous and comprehensive. He graduated from well within the federal executive branch, the climate for restructuring the work of accountability, internal control and government audit. The aim of this study is to create and validate a script, based on use of strategic performance indicators and qualitative, that will guide the new form of surveillance known as Audit Management Assessment, who was born following the restructuring mentioned in the Navy Brazil. To achieve this goal, research is composed of a bibliographical study, including study material from institutions of the Navy for benchmarking and fieldwork consisted of interviews and questionnaires. It was concluded, first, that the bibliographic and documentary studies contributed to the creation of the script evaluation audit of management in the Navy, consisting of strategic and qualitative indicators. Second, the field work with the chosen universe of internal auditors allowed the Navy to consider valid that script, with suggestions for improvement that added more value to it